Development of Jute Fabric for Jute-Polyester Biocomposite considering Structure–Property Relationship: Jute Fabric Structure for Biocomposite. Issue 5 (4th May 2022) - Sengupta, Surajit
ABSTRACT: An attempt has been made to investigate the effect of jute fabric structure, e.g., woven (plain, twill, matte), knitted, and nonwoven (parallel, cross, random laid) as reinforcement, on properties of the jute-polyester composite. The composite sheet was prepared with unsaturated polyester resin and jute fabric by hand lay-up technique using a male-female type mold. Tensile, flexural, impact, and water absorption properties of composite were measured. With the best composite based on properties, compression, shear, and hardness were also measured. Random laid nonwoven shows maximum tensile and impact strength but twill fabric produces maximum flexural strength. Matte fabric shows higher strength and lower elongation among the woven fabrics under experiment. Impact resistance and water absorption of composite from multi-layer fabric are higher compared to single-layer fabric. Composite from twill fabric shows maximum water penetration, whereas random laid nonwoven shows the lowest in similar condition. The study reveals that composite from knitted fabric is better than woven fabric but inferior to nonwoven fabric so far as mechanical properties are concerned. So, multi-layered needle punched jute nonwoven fabric from random laid web is recommended for jute-polyester composite, where higher tensile and impact strength with lower water absorption is required.